Handbook on international corporate governance : country analyses - Mallin, Chris A. (Northampton, Mass., Cheltenham : Edward Elgar Publishing, 2006)
This volume provides a comprehensive analysis of the development of corporate governances across a range of countries, including Australia, Germany, Spain and the UK. It also gives insight into its evolution in countries with diverse cultural, economic and legal systems.
Includes bibliographical references and index.
oif 24/03/15
Loan
Keywords: Corporate governance -- Cross-cultural studies; Comparative management -- Cross-cultural studies; International business enterprises -- Management